Planning to halve Gram-negative bloodstream infection: getting to grips with healthcare-associated Escherichia coli bloodstream infection sources. Issue 2 (February 2019) - Otter, J.A.; Galletly, T.J.; Davies, F.; Hitchcock, J.; Gilchrist, M.J.; Dyakova, E.; Mookerjee, S.; Holmes, A.H.; Brannigan, E.T.
Summary: Background: A thorough understanding of the local sources, risks, and antibiotic resistance for Escherichia coli bloodstream infection (BSI) is required to focus prevention initiatives and therapy. Aim: To review the sources and antibiotic resistance of healthcare-associated E. coli BSI. Methods: Sources and antibiotic resistance profiles of all 250 healthcare-associated (post 48 h) E. coli BSIs that occurred within our secondary and tertiary care hospital group from April 2014 to March 2017 were reviewed. Epidemiological associations with urinary source, gastrointestinal source, and febrile neutropenia-related BSIs were analysed using univariable and multivariable binary logistic regression models. Findings: E. coli BSIs increased 9% from 4.0 to 4.4 per 10, 000 admissions comparing the 2014/15 and 2016/17 financial years. Eighty-nine cases (36%) had a urinary source; 30 (34%) of these were classified as urinary catheter-associated urinary tract infections (UTIs). Forty-five (18%) were related to febrile neutropenia, and 38 (15%) had a gastrointestinal source. Cases were rarely associated with surgical procedures (11, 4%) or indwelling vascular devices (seven, 3%). Female gender (odds ratio: 2.3; 95% confidence interval: 1.2–4.6) and older age (1.02; 1.00–1.05) were significantly associated with a urinary source. No significant associations were identified for gastrointestinal source or febrile neutropenia-related BSIs. Forty-seven percent of the isolates were resistant to ciprofloxacin, 37% to third-generation cephalosporins, and 22% to gentamicin. Conclusion: The gastrointestinal tract and febrile neutropenia together accounted for one-third of E. coli BSI locally but were rare associations nationally. These sources need to be targeted locally to reduce an increasing trend of E. coli BSIs.